Hepatobiliary Phase MRI as a Problem-Solving Sequence for Evaluating Potentially Metastatic Liver Lesions: A Case Series - Dahiya, Aakansha; Baheti, Akshay D.; Ankathi, Suman K.; Choudhari, Amit; Haria, Purvi D.; Guha, Amrita; Kulkarni, Suyash S. (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Background Incidentally detected focal liver lesions in patients with known primary malignancy often pose a diagnostic challenge and are labeled as indeterminate. Utilizing an additional hepatobiliary phase as an adjunct in these cases helps to differentiate potentially metastatic lesions from benign or pseudo lesions.Aim We share three cases where hepatobiliary phase imaging for an indeterminate hepatic observation helped in differentiating benign from metastatic etiology. We also briefly discuss the different appearances of liver lesions in post-chemotherapy patients.Results and Conclusion Out of the three cases, one had a hypointense appearance on the hepatobiliary phase suggesting metastasis, while the other two had iso- or hyperintense appearance suggesting a benign or pseudo lesion.
Keywords: gadobenate dimeglumine; hepatobiliary phase; magnetic resonance imaging; metastasis